2020
DOI: 10.21608/bvmj.2020.37744.1238
|View full text |Cite
|
Sign up to set email alerts
|

Incidance of Psychotropic bacteria in frozen chicken meat products with special reference to Pseudomonas species

Abstract: Total of hundred random samples of frozen chicken products represented by breast, thigh, nuggets and burger (25 of each) were collected from various supermarkets located in Menoufia government. To study the incidence of psychotropic bacteria with special reference to Pseudomonas species. The study revealed that mean values of Psychotropic count were 8.17×10 3 ± 1.42×10 3 , 1.95×10 4 ± 2.06×10 4 , 3.63×10 4 ± 0.89×10 4 and 7.58×10 4 ± 1.16×10 4 respectively while the mean value of Pseudomonas counts were 3.51×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Based on our results, the mean Pseudomonas counts (CFU/g) were 10.1 x 10 3 ± 1.45 x10 3 , 7.4 x 10 3 ± 0.89 x 10 3 , 6.5 x 10 3 ± 6.43 x10 3 and 4.3 x 10 3 ± 7.56 x10 3 for the isolates recovered from the breast, thigh, burger, and nuggets, respectively. Comparable ndings were recorded by Hassan et al (2020), who found that the mean Pseudomonas counts recovered from various chicken meat products (chilled breast, thigh, nuggets and burger) varied from 3.51×10 3 ± 0.76×10 3 to 8.44×10 3 ± 1.85×10 3 . Other parallel records detected by Morshdy et al (2018) and Abd El-Aziz (2015) were 3.6×10 3 and 2.6×10 4 , respectively.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Based on our results, the mean Pseudomonas counts (CFU/g) were 10.1 x 10 3 ± 1.45 x10 3 , 7.4 x 10 3 ± 0.89 x 10 3 , 6.5 x 10 3 ± 6.43 x10 3 and 4.3 x 10 3 ± 7.56 x10 3 for the isolates recovered from the breast, thigh, burger, and nuggets, respectively. Comparable ndings were recorded by Hassan et al (2020), who found that the mean Pseudomonas counts recovered from various chicken meat products (chilled breast, thigh, nuggets and burger) varied from 3.51×10 3 ± 0.76×10 3 to 8.44×10 3 ± 1.85×10 3 . Other parallel records detected by Morshdy et al (2018) and Abd El-Aziz (2015) were 3.6×10 3 and 2.6×10 4 , respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Chicken meat burgers (25/69) and nuggets (25/69) were the most contaminated chicken meat products of Pseudomonas species, which might be a result of mismanagement, extreme usage, and unsuccessful hygienic practices throughout processing and packing. Parallel ndings were obtained by Hassan et al (2020), who identi ed 166 isolates of Pseudomonas species, with a high prevalence of P. uorescens followed by P. alcaligenes, P. stutzeri, P. proteolytica, and P. fragi, while low incidence rates were recorded for P. aeruginosa, P. stutzeri, and P. acidovorans. In another study, Arnaut-Rollier et al (1999) detected 3 species of Pseudomonas (P. fragi, P. lundensis, P. uorescens biovars) from both fresh and refrigerated chicken skin.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, a high prevalence of resistance toward such antibiotic agents was reported by Meng et al (China) [40], Khan et al (Australia) [41], Yayan et al (Germany) [42], and Khan and Faiz (Saudi Arabia) [43]. In a survey conducted by Benie et al [32], P. aeruginosa isolates of meat samples revealed the highest resistance rate toward kanamycin (100%), aztreonam (97.60%), and ciprofloxacin (35.40%). Allydice-Francis and Brown [44] stated that the P. aeruginosa isolates of vegetable samples harbored a high resistance rate toward ceftazidime (79.00%), ciprofloxacin (93.00%), gentamicin (97.00%), and imipenem (100%) antibiotic agents.…”
Section: Discussionmentioning
confidence: 64%
“…ey revealed that unnecessary handling, malpractices, poor hygienic quality of raw materials, particularly spices, and unsanitary practices during production and storage were the main reasons for P. aeruginosa in frozen meat samples. Benie et al [32] reported that the P. aeruginosa prevalence amongst smoked fish, fresh fish, and bovine meat samples collected from West Africa was 23.57%, 37.69% 53.04%, respectively. Up to now, the highest P. aeruginosa prevalence among food samples has been reported by Benie et al [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation